Evaluation of Management of Medical Record Release at Panti Waluya Sawahan Hospital Malang - Tyas Kusumaningrum; Fita Rusdian Ikawati; Anis Ansyori (Universitas Ibn Khaldun Bogor, 2026)
This study aims to evaluate the management of the release of medical records at Panti Waluya Sawahan Hospital Malang based on the Standard Operating Procedure (SPO) document Number RM.32.2022. This type of research is a qualitative descriptive research that describes the results of the evaluation of the release of medical record information at Panti Waluya Sawahan Hospital Malang. The method used is qualitative descriptive with observation techniques through document study and content analysis. The results of the evaluation show that although SPO has established normative requirements and flows for the release of medical information, its implementation still faces various obstacles. Among them are non-compliance of third parties who often do not attach power of attorney, inconsistencies in verification of applicants' identities, lack of service time standards, and reliance on manual documentation. These findings indicate the need to revise SOPs with the addition of technical guidelines for third parties, determination of service times, and the implementation of a digital recording system through SIMRS. These improvements are important to improve data security, service efficiency, and compliance with applicable legal regulations.